Mackerel Fish (Rastrelliger Kanagurta) Management Strategy at Karangantu Port - M Yusuf Ridho; Susiloningtyas, Dewi; Budiharsono, Sugeng (PT Inovasi Pratama Internasional, 2023)
The aim of this research is to understand the management strategy for Mackerel Fish (Rastrelliger Kanagurta) at Karangantu Harbor. The research method used by researchers is a quantitative research method. The sample selection in this research used the primary data sampling technique, using a purposive sampling technique. Because the aim of this research was mackerel, sampling was carried out randomly on the fishing fleet that caught mackerel and landed at PPN Karangantu. Meanwhile, the researcher's data analysis used Catch Per Unit Effort (CPUE), Fox Model, Schaefer Model, Walter-Hilborn Model, Clarke Yoshimoto Pooley (CYP) Model, and Schnute Model, as well as analysis of management strategy preparation using qualitative descriptive analysis methods based on MSY values, JTB, and average annual production/catch at Karangantu Harbor. The results of the research show that the correlation coefficient (R2) at 20 days is 0.9537. The r value is close to 1 (one), indicating a close relationship between length growth and fish weight. The condition of the mackerel fishery in the waters of Serang Regency is experiencing a decline. For the management of mackerel, the size of the nets used to catch mackerel should be enlarged so that fewer fish are caught that are smaller than the size at which the gonads first mature.